Renal artery stenosis as an etiology of secondary hypertension: A case report (Indian Journal of Case Reports, 2026)
Secondary hypertension is often resistant to pharmacologic therapy alone and necessitates identification and management of the underlying cause. This report details a case of a 52-year-old middle-aged female with a history of resistant hypertension secondary to bilateral renal artery stenosis, managed successfully with percutaneous transluminal angioplasty. The case highlights the importance of recognizing renovascular hypertension and timely intervention to prevent complications such as heart failure and renal dysfunction.